A Preliminary study on the use of magnetic, Zamzam, and sea water as mixing water for alkali-activated slag pastes. (20th May 2019) - Rashad, Alaa M.; Ezzat, Mohamed
Highlights: MW exhibited the highest flow value followed by ZW, SW and TW. MW exhibited the highest compressive strength followed by ZW, SW and TW. Using MW, ZW or SW as a mixing water led to an improvement in the microstructure. ZW and SW can accelerate the polymerization process. Abstract: This research is the first attempt to study the possibility of employing magnetic water (MW), Zamzam water (ZW) and seawater (SW) as mixing water for alkali-activated slag (AAS) pastes. The results of workability, pH value, compressive strength and microstructure of different specimens mixed with each type of water were compared with those mixed with tap water (TW). The X-ray diffraction (XRD), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) were used to analyze the results. The results showed that using MW, ZW or SW increased the workability, pH value and compressive strength of AAS pastes. The microstructures of the samples prepared with these water types were modified as confirmed by SEM, whilst the polymerization processes were accelerated as confirmed by TGA. It was found that MW has the height improvement followed by ZW and SW, respectively, whilst TW came in the last place.